Australian recommendations on tapering of biologic and targeted synthetic disease‐modifying anti‐rheumatic drugs in inflammatory arthritis. Issue 10 (20th October 2022) - Whittle, Samuel L.; Glennon, Vanessa; Johnston, Renea V.; Avery, Jodie C.; Bell, J. Simon; Brennan, Sue E.; Fong, Christopher; Hissaria, Pravin; Horgan, Ben; O'Neill, Sean; Pisaniello, Huai Leng; Trevena, Lyndal; et al.
Abstract: Biological and targeted synthetic disease‐modifying antirheumatic drugs (b/tsDMARD) have been an important advance in the management of inflammatory arthritis, but are expensive medications, carry a risk of infection and other adverse effects, and are often perceived as a burden by patients. We used GRADE methodology to develop recommendations for dose reduction and discontinuation of b/tsDMARD in people with rheumatoid arthritis (RA), axial spondyloarthritis (AxSpA) and psoriatic arthritis (PsA) who have achieved a low disease activity state or remission. The recommendations form part of the Australian Living Guideline for the Pharmacological Management of Inflammatory Arthritis, an NHMRC‐endorsed 'living' guideline, in which recommendations are updated in near real‐time as new evidence emerges. Conditional recommendations were made in favour of dose reduction in RA and AxSpA but not in PsA. Abrupt discontinuation of b/tsDMARD is not recommended in any of the three diseases.